Data Mining Based Establishment and Evaluation of Porcine Model for Syndrome in Traditional Chinese Medicine in the Context of Unstable Angina (Myocardial Ischemia) - Zhao, Huihui; Chen, Jianxin; Shi, Qi; Wang, Wei (IntechOpen, 2011)
None